Catecholamine levels in plasma and CSF in migraine. Issue 10 (October 1993) - Martínez, F; Castillo, J; Pardo, J; Lema, M; Noya, M
Abstract : There is clinical and pharmacological evidence of the existence of sympathetic dysfunction in migraine. Adrenaline and noradrenaline concentrations were determined in plasma and CSF of patients during attacks of common or classic migraine, comparing them with controls suffering from stress. Plasma noradrenaline levels were significantly lower in the patients with common migraine than in controls (p < 0.05). Other catecholamine levels in plasma and CSF in both migraine groups were only slightly lower than in controls. Our results suggest that central sympathetic dysfunction exists in patients with migraine.